Perancangan Identitas Visual UMKM Solidosol: Strategi Komunikasi Grafis dalam Penguatan Brand Lokal - Refli Saputra; Vanesha Maulin Utari; Tiara, Tiara (CV. ITTC INDONESIA, 2025)
MSMEs are the backbone of the Indonesian economy, yet many businesses have yet to fully utilize the power of visual design. This study examines the MSME Solidosol—a shoe repair and sole manufacturing service—as the target of graphic communication to strengthen its brand image. The objective of this study was to design a professional and consistent visual identity through logo design, supporting visual elements, and promotional media. The methods used included field observation, interviews, manual sketching, and design digitization using Canva. The resulting design was applied to the main logo, color palette, typography, and offline and digital promotional media. The resulting visual identity is expected to enhance Solidosol's appeal and credibility in the eyes of consumers.